Between Shades of Gray : Graphic Novel - Donkin, Andrew; Kopka, Dave; Livesay, Brann; Dickey, Chris; Sepetys, Ruta. (New York : Philomel Books, 2021)
In 1941, fifteen-year-old Lina, her mother, and brother are pulled from their Lithuanian home by Soviet guards and sent to Siberia, where her father is sentenced to death in a prison camp while she fights for her life, vowing to honor her family and the thousands like hers by burying her story in a jar on Lithuanian soil. Based on the author's family, this adaptation includes a historical note.
Keywords: Sepetys, Ruta -- Adaptations; Labor camps -- Comic books, strips, etc; Survival -- Comic books, strips, etc; Labor camps -- Fiction; Survival -- Fiction; Cartoons and comics; Lithuania -- Comic books, strips, etc. -- History -- Soviet occupation, 1940-1941; Siberia (Russia) -- Comic books, strips, etc. -- History -- 20th century; Soviet Union -- Comic books, strips, etc. -- History -- 1925-1953; Lithuania -- Fiction. -- History -- Soviet occupation, 1940-1941; Siberia (Russia) -- Fiction. -- History -- 20th century; Soviet Union -- Fiction. -- History -- 1925-1953; Graphic novel adaptations; Graphic novels